Performance Studies from a short-sighted point of view (Mantichora. Italian Journal of Performance Studies, 2020)
What is Performance Studies? What is Performance? What is the role of a fieldworker trying to understand what Performance Studies does? This is a brief consideration related to a wider attempt of approaching the phenomenon of Performance Studies "as performance", studying it through the methodological lens of the field itself. A work in progress for a "discipline in progress"; both things crossing borders, cultures, genres, methodologies.